ANALYSIS COMPARISON OF PT. BANK CENTRAL ASIA TBK. WITH PT. BANK NEGARA INDONESIA TBK. - Fanani, Winda Atikah; Pardistya, Irvan Yoga (Peneliti.net, 2023)
The comparison of PT's financial performance is the aim of this study.Central Asia Trust Bankis a private bank that ranks second on the IDX, behind only PT.Tbk. Bank Negara IndonesiaThe third-ranked state-owned bank on the IDXFinancial ratios are an instrument that can be utilized to measure financial performance, and both banks have advantages and disadvantages when it comes to managing their financial performance.The comparison of PT's financial performance will be the focus of this study.Central Asia Trust Bankusing PT.Tbk. Bank Negara Indonesiautilizing financial ratios for the years 2015 through 2019.This study relies on secondary information from the annual report of PT.BCA Tbk.as well as PT's annual report.TBD BNIfrom 2015 to 2019.It includes five measured financial ratios—LDR, ROE, ROA, NPL, and OEOI—based on the entire analyzed financial performance.Secondary data from BCA and BNI's annual financial statements, which are listed on the Indonesia Stock Exchange from 2015 to 2019, were used.